One-pot synthesis of nano-EMD for effective adsorption of toxic dyes. - Biswal, Avijit; Dhal, Jyoti Prakash; Das, Bijnyan Ranjan; Panda, Prasanna Kumar; Tripathy, Bankim Chandra (Transactions of the Charles S. Peirce Society)
A simple electrochemical technique was employed to synthesize nanocorn electrolytic manganese dioxide (MnO) (EMD) in the presence of the structure-directing agent poly(vinylpyrrolidone) (PVP) at the optimum concentration in an aqueous acidic manganese sulfate bath. X-ray diffraction and scanning electron microscopy analyses confirmed the formation of γ-manganese dioxide with nanocorn-shaped crystals at the optimum concentration – namely, 20 mg/l PVP. The finely ground material was successfully employed in the removal of the toxic dyes Chicago sky blue (CSB) and malachite green (MG) from aqueous solution. Various process parameters such as different adsorbents, adsorbent dose, contact time, initial dye concentration and pH were varied and optimized for both dyes. It was found that EMD showed 99.61% adsorption efficiency at an optimum dose of 0.04 g/20 ml of the 100 mg/l CSB dye solution at room temperature within 20 min. However, the same EMD sample showed 99.5% adsorption efficiency at an optimum dose of 0.07 g/20 ml of the 100 mg/l MG dye solution at room temperature within 120 min. From the adsorption kinetics study, it was concluded that the adsorption process follows pseudo-second-order kinetics and the adsorption isotherm confirms that the reaction follows Langmuir adsorption for both dyes.